The Impact of Financial Access on Income Inequality: Evidence from Panel Data Estimation - Arestis, Philip; Eng, Khai Ying (Panoeconomicus, 2025)
As there are limited attempts made by previous studies, this paper examines the impacts of financial access on income inequality using a panel data of 52 developed and developing countries ranging from 2005 to 2020. Initially, the Financial Access Survey (FAS), launched in 2009 suggested that demographic and geographical data of bank branches and automated teller machine (ATM) able to reflect the accessibility of financial service and UN SDG also adopted the demographic data of bank branches and automated teller machine in the SDG target goal as an alternative to expand financial access and strengthen the capacity of domestic financial institution. To measure financial access effectively, indicators such as the number of bank branches and automated teller machines per thousand square feet and hundred thousand adults are employed in this paper to proxy financial access and examine its impact on income inequality. In addition, since the empirical model is largely unexplored, this paper aims to examine the issue thoroughly with secondary data that cover a broader duration and capture changes within the same observation over time. Dynamic panel system generalized method of moments (GMM) estimators is used and the empirical result grounded in real-world data could adopt the outputs, which disclose the relative strength of the influence of financial access on income inequality and identify whether access to finance is useful to narrow down income inequality. The conclusions are also critical for policy design as well.JEL: G20, E25, C33, D31